A legitimista, a monarchista és a republikánus. Adalékok Mindszenty bíboros, Hamvas püspök és Balogh páter kapcsolatához 1946-ból - Miklós, Péter (Közép-Európai Közlemények, 2014)
Cardinal József Mindszenty, like many other high priest between the two world wars, was traditionally Habsburg-royalist sympathies, Bishop Endre Hamvas’s opinion was the ideal form of government is the monarchy (according to contemporary teaching of Catholicism), the catholic priest István Balogh – who was working as a sectretery of state between 1944 and 1947 – supported the republic in Hungary. In 1946, after the proclamation of the Republic of Hungary, the relationship deteriorated between the cardinal, the bishop and the priest%politician. On the one hand, the Hungarian Catholic leaders reluctantly admitted the new form of government, the other hand, the left-wing parties in the spring of 1946 launched a strong attack against the reactionary think Cardinal Mindszenty. At the time, Stephen Balogh was not out by the high priests, which makes it superior of a religious, Bishop Hamvas, received canonical admonishment. The topic of present study is the relations of the cardinal, the bishop and the secretary of state and the paper’s sources was church archives documents and contemporary secret police reports.